163k views
4 votes
To make the expression 4x-2 + (2x + 4) equivalent to 2(6x + 7), what must be the value in the box?

User Ketiwu
by
5.8k points

1 Answer

4 votes


4x - 2 + (2x + 4) = 2(6x + 7) \\


4x - 2 + 2x + 4 = 12x + 14

Simplification


6x + 2 = 12x + 14

Subtract sides 2


6x + 2 - 2 = 12x + 14 - 2

Simplification


6x = 12x + 12

Subtract sides -12x


6x - 12x = 12x - 12x + 12

Simplification


- 6x = 12

Divided sides by -6


( - 6)/( - 6)x = (12)/( - 6) \\


x = - 2

It is must be in the box buddy.

And we're done...♥️♥️♥️♥️♥️

User Superdesk
by
4.6k points